2018
DOI: 10.1016/j.tiv.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of pristine graphene monolayer: Scaffold for fibroblasts

Abstract: The aim of the present study was to evaluate the cytotoxicity of pristine graphene monolayer and its utility as a scaffold for murine fibroblast L929 cell line. Cell viability, morphology, cytoskeleton architecture (microfilaments and microtubules), cell adhesion and migration into the scratch-wound area were determined using pristine graphene-coated microscopic slides. We found that fibroblasts cultured on pristine graphene monolayer exhibited changes in cell attachment, motility and cytoskeleton organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 47 publications
2
39
1
Order By: Relevance
“…Pristine single-layer GR cytotoxicity, as well as the possibility of its application for the scaffold preparation for the L929 mouse fibroblast cell line, was studied in [79] by observing cell viability, cell adhesion, morphology, cytoskeleton architecture, and movement to the scratch-wound area. It was confirmed that GR was not cytotoxic for the L929 cell line and conversely enhanced the adhesion of cells and their proliferation within 24 h [79]. GBMs have a number of outstanding properties which make them very suitable materials for regenerative medicine, especially for growth of stem cells, such as their proliferation and differentiation ability.…”
Section: Nanotheranostics and Tissue Engineeringmentioning
confidence: 99%
“…Pristine single-layer GR cytotoxicity, as well as the possibility of its application for the scaffold preparation for the L929 mouse fibroblast cell line, was studied in [79] by observing cell viability, cell adhesion, morphology, cytoskeleton architecture, and movement to the scratch-wound area. It was confirmed that GR was not cytotoxic for the L929 cell line and conversely enhanced the adhesion of cells and their proliferation within 24 h [79]. GBMs have a number of outstanding properties which make them very suitable materials for regenerative medicine, especially for growth of stem cells, such as their proliferation and differentiation ability.…”
Section: Nanotheranostics and Tissue Engineeringmentioning
confidence: 99%
“…Graphene films can be transferred onto a wide range of substrates 53,55 and are used in both physics 69 and biology (eg, surfaces for cell growth). 70 While graphene solutions, in which graphene flakes and sheets are formed, are employed in the majority of toxicological studies 65,68,[71][72][73] involving the dispersion of graphene in biological fluids, much less attention has been devoted to the biocompatibility of graphene in the form of a monolayer 63,70,[74][75][76] which can be used as a scaffold for the…”
Section: Graphene Properties With Respect To Biology (Wettability Namentioning
confidence: 99%
“…The extracellular parts of integrins bind to the ECM, their integral parts anchor integrin into the cell membrane and their intracellular parts bind to the focal adhesion proteins thus forming a physical link between the ECM and the actin cytoskeletal network. 63,82,83 Focal complexes that connect cells with the external environment are crucial for the functioning of cellular processes and mechanisms such as mechano-sensoring, spreading, cell migration and proliferation. 84 The focal adhesion assembly responds to matrix stiffness, 85 a phenomenon that is used by researchers for the qualitative and quantitative analysis of the effect on cellular behavior of the nanotopography of the various substrates used in regenerative medicine.…”
Section: Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to mixing graphene particles with biomaterial components, we transferred pristine graphene layers onto the Am surface, which didn't have contact with cytotoxic or cross-linking substances. Nonchemically-modified graphene is considered to be the most biocompatible form of graphene as it was shown not to alter neuron or muscle cell activity and simultaneously creates a favorable environment for electrical charge transfer 32 . As far as biocomposite structure is concern the next step should comprise evaluation of graphene layer structural coherency using Atomic Force Microspcopy (AFM).…”
Section: Discussionmentioning
confidence: 99%